2015
DOI: 10.1111/bph.13269
|View full text |Cite
|
Sign up to set email alerts
|

Combining citrulline with atorvastatin preserves glucose homeostasis in a murine model of diet‐induced obesity

Abstract: BACKGROUND AND PURPOSENO is a crucial regulator of energy and lipid metabolism, whose homeostasis is compromised during obesity. Combination of citrulline and atorvastatin potentiated NO production in vitro. Here we have assessed the effects of this combination in mice with diet-induced obesity (DIO). EXPERIMENTAL APPROACHC57BL/6J male mice were given a standard diet (control) or a high fat-high sucrose diet (DIO) for 8 weeks. DIO mice were then treated with DIO alone, DIO with citrulline, DIO with atorvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A total of 16 ApoE-deficient mice were additionally divided into two groups and received a high-fat diet in addition to the treatment described above. As previously suggested by Capel et al ( 8 ), a 10 mg dose of atorvastatin has been repeatedly demonstrated to be effective on lipid metabolism in mice, and the relevant literature is listed in Table I ( 8 17 ). All mice were individually housed in plastic cages (30×20×13 cm) throughout the extent of the present study and maintained on a 12/12 h light/dark cycle (light off at noon) at constant temperature (22°C) with 10–15 hly cycles of fresh air and relative humidity (60±10%).…”
Section: Methodsmentioning
confidence: 94%
“…A total of 16 ApoE-deficient mice were additionally divided into two groups and received a high-fat diet in addition to the treatment described above. As previously suggested by Capel et al ( 8 ), a 10 mg dose of atorvastatin has been repeatedly demonstrated to be effective on lipid metabolism in mice, and the relevant literature is listed in Table I ( 8 17 ). All mice were individually housed in plastic cages (30×20×13 cm) throughout the extent of the present study and maintained on a 12/12 h light/dark cycle (light off at noon) at constant temperature (22°C) with 10–15 hly cycles of fresh air and relative humidity (60±10%).…”
Section: Methodsmentioning
confidence: 94%
“…Some of these studies showed a direct effect of Cit on adipocytes via a NO-dependent process, and on muscle cells through PI3K/MAPK/4E-BP1 signalling ( 13 , 26 ) . Cit supplementation is also associated with improved insulin sensitivity ( 27 ) and endothelial function ( 28 ) . Interestingly, in the experiments of the present study, Cit supplementation was found to be associated with higher plasma Arg, a trend toward normalisation of the Arg:Orn+Cit ratio – a marker of global Arg availability for NO synthesis ( 23 ) – and with a higher Arg:Lys ratio – a marker of Arg entry into the cells ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…CIT ingestion by healthy aged rats increased muscle mitochondrial density and TFAM (a mitochondrial transcription factor) expression . CIT supplementation also increased energy expenditure in obese mice and, as a malate salt, improved phosphocreatine regeneration after exercise in humans . Moreover, CIT has been shown to affect lipid metabolism …”
Section: Introductionmentioning
confidence: 99%